How teacher rotation in Japanese high schools affects the clustering of teacher quality: Comparing the distribution of teachers across public and private education sectors - Seebruck, Ryan (Education Policy Analysis Archives, 2021)
I examine a unique facet of Japan’s public education system: jinji idou, a mandatory teacher rotation system governed by the prefectural board of education where teachers are systematically transferred to other schools throughout their careers to appropriately staff schools, facilitate varied career paths, and identify future leaders for administrative roles. Although not a formal goal, this centralized system may also produce a more equal distribution of teacher quality across schools compared to the decentralized teacher labor market found in private schools. Because this system is present in public schools and absent in private schools, comparing sector differences offers a look at its impact on teacher quality distribution. Using a sample of 1,456 teachers nested in 49 schools, private vs. public group comparison tests indicate that, for most of the teacher quality traits examined, the public sector distributes teachers more equitably. Furthermore, the public sector has higher mean levels of teacher quality, intimating that education labor markets can be structured in ways that simultaneously minimize variation between schools without hindering quality, findings germane to scholars interested in educational equality.